Who they are versus what they want: How dominance, influence, steadiness, and compliance profiles can aid in developing employability. Issue 6 (December 2022) - Fertig, Jason; O'Neill, Bonnie S.; Wells, Pamela; Bassil, Carelle B.
This paper draws attention to a behavior-based assessment instrument that is frequently utilized in industry settings but less utilized in the academic classroom. The authors argue that this instrument, the dominance, influence, steadiness, and compliance (DISC) profile, can be useful in training and developing soft skills desired by employers. They also examine the effects of gender and work experience on the various DISC patterns to better understand how this instrument may be useful for coaching and mentoring in those academic and organizational contexts. In this study, DISC pattern data were gathered from 1547 undergraduate and graduate students across multiple universities in the USA. A multivariate analysis of variance was performed on the data and the results show males scoring higher on Dominance and females scoring higher on Steadiness, as predicted. Females scored higher on Compliance, contrary to predictions. Graduate students scored higher on Dominance and undergraduates scored higher in Steadiness, as hypothesized. Undergraduates also scored higher on Influence than did graduate students. Such differences in DISC profiles suggest that, as a behavior-based instrument, DISC may be helpful for students in understanding their behavioral tendencies as well as identifying workplace behaviors needed to bridge the gap between the soft skills employers want and the competencies students possess.